Laparoscopic excision of an ascending colon duplication cyst in an adolescent - Heather R. Nolan (Journal of Pediatric Surgery Case Reports, 2016)
Colonic intestinal duplications are infrequent and rarely present past early childhood. We present the case of a large, ascending colon duplication in a 17-year-old boy resected using minimally invasive techniques. This appears to be the first reported case of a laparoscopic en-bloc ascending colon duplication resection in an adolescent. The diagnosis and management of colonic duplications are discussed.